2023
DOI: 10.1021/acs.jctc.3c00087
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Accuracy Limits of PNO-Based Local Coupled-Cluster Calculations for Transition-Metal Complexes

Abstract: While the domain-based local pair natural orbital coupled-cluster method with singles, doubles, and perturbative triples (DLPNO-CCSD(T)) has proven instrumental for computing energies and properties of large and complex systems accurately, calculations on first-row transition metals with a complex electronic structure remain challenging. In this work, we identify and address the two main error sources that influence the DLPNO-CCSD(T) accuracy in this context, namely, (i) correlation effects from the 3s and 3p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Similar deviations were observed for some of the extrapolated values, especially those obtained from (5/6) extrapolation (e.g., neutral Pt–CO at a multiplicity 3 with def2-SVP basis set). Again, this could be traced back to similar issues observed in the MOBH35 data set. , …”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Similar deviations were observed for some of the extrapolated values, especially those obtained from (5/6) extrapolation (e.g., neutral Pt–CO at a multiplicity 3 with def2-SVP basis set). Again, this could be traced back to similar issues observed in the MOBH35 data set. , …”
Section: Resultssupporting
confidence: 54%
“…Again, this could be traced back to similar issues observed in the MOBH35 data set. 55,72 We have found that the proposed scheme provides a welldefined increase in the accuracy with minor dependence on the basis set size (Figure 1). This finding is of special importance because of the recently published result stating the dependence of the DLPNO error on this parameter.…”
Section: Metal−co Interactionsmentioning
confidence: 85%
“…The exciting development of localized orbital approximations, such as, e.g., the PNO-LCCSD­(T)-F12 and DLPNO-CCSD­(T) implementations, when appropriately converged, can also be readily used in these regimes to provide reliable reference values. With these localized coupled cluster implementations, the use of extended basis sets is possible, and thus, a more realistic evaluation of DFT methods as well as a comparison with experimentally measured ionization energies.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Later, a revision to their DLPNO-CCSD(T) references was suggested on the grounds of static correlation effects, 50 but a study by Altun et al traced the DLPNO error to correlation effects from the 3s and 3p semicore orbitals and to dynamical correlation-induced orbital relaxation effects. 51 In another study, the DLPNO approach performed well for challenging spin-splitting energies of iron complexes and reproduced CASPT2/CC results with a twopoint PNO extrapolation and improved full iterative triples. 52 Results of similar quality were found for the ionization energy of cobaltocene.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation